A case report of placental mesenchymal dysplasia: A rare case of a genetically normal fetus with severe intrauterine growth restriction. Issue 8 (February 2019) - Doroftei, Bogdan; Neculai-Valeanu, Sabina; Simionescu, Gabriela; Grab, Delia; Plopa, Natalia; Anton, Emil; Maftei, Radu
Abstract: Rationale: We report a rare case of a pregnant woman with placental mesenchymal dysplasia (PMD) and intrauterine growth restriction (IUGR) with a genetically normal fetus. Patient concerns: A 42-year-old woman Gravida I, Para I with pre-existent uncontrolled hypertension and uterine polyfibromatosis present at 30 weeks of gestation for diminished fetal activity during the last 2 days. Diagnosis: Placental mesenchymal dysplasia associated with intrauterine growth restriction, hypertension, and uterine polyfibromatosis. Intervention: A live male infant was delivered by emergency caesarean section. Outcomes: The infant, weighing 700 g, died 4 days after birth due to a massive intracerebral hemorrhage. Lessons: A careful examination should be done at every ultrasound in case of a fetus with IUGR to exclude some rare cases of placental pathologies. PMD can be a rare cause of IUGR with a genetically normal fetus.